DE 201: A practitioner's guide to developmental evaluation - Dozois, Elizabeth; Langlois, Marc; Blanchet-Cohen, Natasha (J.W. McConnell Family Foundation, 2010)
Developmental evaluation has emerged fairly recently as a way to suppo rt adaptive learning in complex and emergent initiatives. Combining th e rigour of evaluation with the flexibility and imagination required f or development, this new form of evaluation brings critical thinking t o bear on the creative process in initiatives involving high levels of uncertainty, innovation, emergence, and social complexity. This guide book from J.W. McConnell Family Foundation and the International Insti tute for Child Rights and Development explores key aspects of Developm ental Evaluation (DE) and offers suggestions for implementing the prac tice and includes a range of DE resources to help with its facilitatio n. Contents What is developmental evaluation? When is developmental ev aluation appropriate? What competencies are needed to be an effective DE? How is developmental evaluation practiced? Challenges Appendices A ssessing Readiness Stakeholder analysis Sample Learning Framework Syst ems Analysis Framework - Key Components Data Analysis Resources